Evaluation of Mechanical Properties, Economic and Environmental Benefits of Partially Replacing Silica Sand with Biomass Ash for Aluminium Casting. (2018) - Srinivasan, Karthick; Siddharth, C.S.K.; Kaarthic, L.V. Arun; Thenarasu, M.
Abstract: Green sand molding for metal casting makes up around 70% of the total castings produced worldwide. Silica sand mining and its transportation to foundries harm the ecosystem, rendering this metal casting process environmentally unsustainable. This research paper introduces a novel method of partially replacing the silica sand with biomass ash - a waste product of combustion in various processes such as domestic and commercial cooking. Suitable experiments were conducted to measure the effects of mixing progressively higher proportions of biomass ash (from 9% to 30%) in conventional green sand mold. The molds then underwent tests for the evaluation of technological properties such as green compression strength, green shear strength, permeability and compaction. After suitable pattern making, the molds were tested for casting using LM 24 Aluminium Alloy. The obtained Aluminium Alloy castsings underwent micro hardness tests and micro structure study. The results obtained for biomass ash molding sand were compared with the corresponding tests results for conventional sand mold casting and the results were satisfactory.